A Modelling Study of Post-Combustion Capture Plant Process Conditions to Facilitate 95–99% CO2 Capture Levels From Gas Turbine Flue Gases - Michailos, Stavros; Gibbins, Jon (Frontiers in Energy Research, 2022)
The principal purpose of this study is to examine the changes in process conditions that might be needed to achieve up to 99% capture levels in amine post-combustion capture (PCC) plants for combined cycle gas turbine (CCGT) flue gases. This information is of interest since, while 95% capture is adequate for current market and regulatory conditions, net zero fossil emissions (99% capture for a CCGT plant) will be required to deliver global climate mitigation targets and is increasingly a target for national climate policies. The conventionally-configured plant in the study is based on FEED studies carried out by Bechtel Corporation and uses MEA at 35% w/w. Performance modelling is undertaken using the Aspen Plus CCSI MEA Steady State Model. The results show that efficient operation at higher capture levels appears to be feasible with minimal adjustments to the plant configuration, provided that the absorber has a sufficient packing height and the stripper is capable of operation at pressures above 2 bar. The study primarily focuses on operation at low lean loadings (0.09–0.15 molCO2/molMEA) and correspondingly low L/G ratios (<1 by mass), the combination of which, in principle, can give a higher rich loading for a given capture level and packing height and consequently reduce energy consumption. However, for a given capture level, there is a minimum absorber packing height below which a near-optimal rich loading cannot be achieved for any lean loading and L/G ratio. For example, at a lean loading of 0.12 molCO2/molMEA, an absorber packing height of approximately 24 m is required for 99% capture with a minimal increase in specific energy requirements (3.77 GJ/tCO2 at 99% capture vs. 3.50 GJ/tCO2 at 95% capture). A stripper pressure of 2.4 bar is also found to be necessary to achieve this lean loading level without excessive energy requirements. The effect of varying lean loading at three constant rich loading levels is reported in detail, as are the effect of rich loading at constant lean loading and the effect of pressure on stripper performance and energy requirements. The study also examines the effects of cooling and intercooling at elevated capture levels. A simple analysis of break-even operating costs suggests that capture levels higher than the 95% envisaged in current United Kingdom guidance, to further reduce CO2 emissions costs for CCGT + PCC, might be attractive if carbon dioxide removal from air is the alternative.